LANGUAGE PRODUCTION DISORDER OF A BROCA APHASIC (A CASE STUDY) - PANGGALIH, PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Panggalih, Putri, 2014. Language Production Disorder by A Broca Aphasic (A Case Study).  Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Fatimah; Co-supervisor: Yana Shanti Manipuspika  Keywords:  Broca Aphasia, Broca Aphasic, Language Production Disorder Human beings use language  in completing complex systems of communication. Language production occurs in the human brain. One of language disorders  caused by the damage of the brain is called aphasia.  There are three broad categories of aphasia: fluent or Wernicke aphasia, non-fluent or Broca aphasia, and pure aphasia or Alexia. In this study, the writer only investigated the language production disorder  of someone suffer’s from  Broca aphasia.  This disorder will trouble someone in producing the language. The aim of this study was to find out the characteristics of language production of Mr. Arifin as a Broca aphasic. This study used  qualitative approach because it analyzed  the language production disorder from a Broca aphasic. Case study was applied in this study to get the detail description from the subject. To investigate the language production disorder from the Broca aphasic, the writer did interview and analyzed  the characteristics by using theory from Garman (1990). The data of this study were utterances produced by Mr. Arifin. This study revealed that there are seven  characteristics of language production of Broca aphasic encountered by Mr. Arifin. Those are the output rate is low, the utterances have articulation disorder, are typically short, have  fluency disorder, have disruption of normal intonational patterns,  often omits  the formation of affixes and function words, and mostly concern in content words. The writer found that the subject found difficulties in producing clear articulation, getting fluency disorder, and producing short utterances as the major characteristics encountered by Mr. Arifin. In this study, the writer concluded that Mr. Arifin cannot produce language as fluent as other people since he encounters seven characteristics  of Broca aphasia.  Producing language will give him hard situation and  trigger  language production disorder during speech. However, the result of this study cannot be generalized to other Broca aphasia cases.    The last, the writer suggests  the readers to be aware of the characteristics of Broca aphasia by knowing the  characteristics  of a Broca aphasic. Next, the writer suggests to the next  researcher who wants to analyze  the same field to compare the characteristics of language production disorder of a Broca aphasic with other aphasia. It  is to enhance and enrich the study about language disorder, especially aphasia that is still limited in number in Indonesia.